2013
DOI: 10.1074/jbc.m113.459222
|View full text |Cite
|
Sign up to set email alerts
|

Hemolymph Melanization in the Silkmoth Bombyx mori Involves Formation of a High Molecular Mass Complex That Metabolizes Tyrosine

Abstract: Background:The phenoloxidase (PO) cascade regulates the melanization of blood in insects and other arthropods. Results: Hemolymph from Bombyx mori rapidly melanizes after wounding and forms a complex that uses tyrosine as the substrate. Conclusion: Tyrosine usage requires formation of a phenoloxidase-containing complex. Significance: Processing of prophenoloxidase is an intermediate step in the phenoloxidase cascade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 54 publications
1
51
0
Order By: Relevance
“…By identifying 66 proteins (10 -80 kDa) in gel slices 1-3 (80 to Ͼ200 kDa) (Table S5), we validated and extended the previous observations of such complexes (16,19,43,45,46). Nearly half (32) of them (e.g.…”
Section: Table II Distribution Of Selected Immunity-related Proteins supporting
confidence: 66%
“…By identifying 66 proteins (10 -80 kDa) in gel slices 1-3 (80 to Ͼ200 kDa) (Table S5), we validated and extended the previous observations of such complexes (16,19,43,45,46). Nearly half (32) of them (e.g.…”
Section: Table II Distribution Of Selected Immunity-related Proteins supporting
confidence: 66%
“…The endogenous pattern recognition proteins and proHP1 in plasma apparently do not initiate the system under the normal physiological condition. Perhaps, spontaneous oligomerization of these system components can trigger melanization and additional association of the oligomers on microbial surfaces enhance the potency and locality of this response (Yu et al, 2003; Clark and Strand, 2013; He et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is plausible that B. mori C-type lectins play important roles not only in the recognition of invading pathogens, but also in the initiation of proPO activation by means of BmSPH1 and BmSPH2. Clark and Strand (2013) reported that SPH1 and a kind of C-type lectin (C-type lectin 21) formed a complex with PO in B. mori (Clark and Strand, 2013). Thus, protein complexes consisting of BmSPH1, BmSPH2 and B. mori C-type lectins observed in our examination (Fig.…”
Section: Bmsphs In Plasma Are Concentrated In Nodules By B Mori Ctypmentioning
confidence: 47%
“…Thus, protein complexes consisting of BmSPH1, BmSPH2 and B. mori C-type lectins observed in our examination (Fig. 3) might be precursors of the PO-containing complex observed by Clark and Strand (2013). It is possible that protein complexes consisting of BmSPH1, BmSPH2 and B. mori C-type lectins help PO to congregate around the surface of pathogens, resulting in the melanin deposition on the pathogens.…”
Section: Bmsphs In Plasma Are Concentrated In Nodules By B Mori Ctypmentioning
confidence: 63%